THE IMPORTANCE OF TEACHING READING: : IMPROVING STUDENTS’ READING COMPREHENSION IN EFL CONTEXT EMPHASIZED ON READING FLUENCY AND ACCURACY - Muhammad Rochman (UIBU, 2018)
Current methods for teaching reading comprehension tend to emphasize the products of comprehension and neglect the processes of comprehension. Teachers often provide insufficient opportunities for learners to practice English in teaching reading. During teaching reading in a class teachers may confuse to give exercises relate to fluency or accuracy. The correlation between fluency and reading comprehension showed a significant positive relationship between oral reading fluency and reading comprehension performance. Therefore, automaticity of decoding fluency is essential for high levels of reading achievement. Assessing reading fluency, teachers need to listen to students read aloud to make judgments about their progress in reading fluency. In other side, teaching reading in accuracy exercises encourage a thoughtful use of language and the information is intended to help students understand how English works.